Positive geothermal anomalies in oceanic crust of Cretaceous age offshore Kamchatka - G. Delisle (Solid Earth, 2011)
Heat flow measurements were carried out in 2009 offshore Kamchatka during the German-Russian joint-expedition KALMAR. An area with elevated heat flow in oceanic crust of Cretaceous age – detected ~30 yr ago in the course of several Russian heat flow surveys – was revisited. One previous interpretation postulated anomalous lithospheric conditions or a connection between a postulated mantle plume at great depth (>200 km) as the source for the observed high heat flow. However, the positive heat flow anomaly – as our bathymetric data show – is closely associated with the fragmentation of the western flank of the Meiji Seamount into a horst and graben structure initiated during descent of the oceanic crust into the subduction zone offshore Kamchatka. This paper offers an alternative interpretation, which connects high heat flow primarily with natural convection of fluids in the fragmented rock mass and, as a potential additional factor, high rates of erosion, for which evidence is available from our collected bathymetric image. Given high erosion rates, warm rock material at depth rises to nearer the sea floor, where it cools and causes temporary elevated heat flow.